2022
DOI: 10.1186/s12909-022-03594-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an inexpensive short-term theoretical-practical course on videosurgery for surgeons in training

Abstract: Background The rapid development of video surgery and minimally invasive surgical techniques prompted many studies on the methods of teaching these techniques to young surgeons in training. However, the characteristics of a short-term course that is both easily accessible and efficient for this group of surgeons remain controversial. To investigate this issue, a short-term training method was proposed for first year surgery residents, using inexpensive handmade wooden simulation boxes with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A brief study was conducted on a realistic laparoscopic course for surgical training using a smartphone camera and a handcrafted wooden simulator box. The findings revealed that people with prior gaming experience needed less time to complete the laparoscopic stitching in the simulator box 6 . The surgical trainee’s performance in difficult procedures, such as knot tying, minimally invasive surgical skill environments, and camera navigation in laparoscopic surgery, was improved by COVID-19 virtual reality simulator training 7 .…”
mentioning
confidence: 98%
“…A brief study was conducted on a realistic laparoscopic course for surgical training using a smartphone camera and a handcrafted wooden simulator box. The findings revealed that people with prior gaming experience needed less time to complete the laparoscopic stitching in the simulator box 6 . The surgical trainee’s performance in difficult procedures, such as knot tying, minimally invasive surgical skill environments, and camera navigation in laparoscopic surgery, was improved by COVID-19 virtual reality simulator training 7 .…”
mentioning
confidence: 98%